Not with my own: Long-term effects of cross-country collaboration on subsidiary innovation in emerging economies versus advanced economies - ALNUAIMI, Tufool (Institutional Knowledge at Singapore Management University, 2012)
Prior literature has established that international collaboration on R&D is an important means for generating new and impactful ideas through the cross-border integration of knowledge. We show that cross-country collaboration improves not just the resulting ideas, but also has a long-term benefit for the involved inventors in terms of continuing to generate higher-impact ideas in the future. However, our results also show that the improved performance of specific inventors in a multinational corporation subsidiary does not translate to broader subsidiary-level capabilities at innovation. One possible explanation might be that inventors obtaining international exposure often do not develop collaborative ties with other inventors in the subsidiary, favouring instead to collaborate internationally on subsequent R&D projects.